Answer:
see explanation
Step-by-step explanation:
h(x) + k(x) = x² + 1 + x - 2 = x² + x - 1
(h + k)(2) = 2² + 2 - 1 = 4 + 2 - 1 = 5
h(x) - k(x) = x² + 1 - (x - 2) = x² + 1 - x + 2 = x² -x + 3
(h - k)(3) = 3² - 3 + 3 = 9 - 3 + 3 = 9
h(2) = 2² + 1 = 4 + 1 = 5
k(3) = 3 - 2 = 1
3h(2) + 2k(3) = (3 × 5) + (2 × 1) = 15 + 2 = 17
Answer:
2.5X=1.0 try this i think
Step-by-step explanation:
tRY THAT
Answer:
Step-by-step explanation:
V = 1/3 * pi * r^2 * h
d = 12
r = d/2
r = 12/2
r = 6
V = 1/3 * 3.14 * 6^2 * 8
V = 301.44